Effect of Non-alcoholic Fatty Liver Disease on the Risk of Synchronous Liver Metastasis: Analysis of 451 Consecutive Patients of Newly Diagnosed Colorectal Cancer - Lv, Yan; Zhang, Hai-jun (Frontiers in Oncology, 2020)
Background: The purpose of this study was to investigate the effect of non-alcoholic fatty liver disease (NAFLD) on the risk of synchronous colorectal liver metastasis (synCRLM). Methods: A retrospective analysis was performed on 451 consecutive patients with newly diagnosed colorectal cancer (CRC) from January 2014 to January 2019. According to the presence of NAFLD, the CRC patients were divided into two groups, NAFLD group (60 cases) and the control group (391 cases). The clinicopathological features and the prevalence of synCRLM between the two groups were compared. Logistic regression analysis was used to analyze the risk factors of synCRLM. Different noninvasive liver fibrosis scoring models were used to evaluate the effect of advanced fibrosis and cirrhosis stage in NAFLD on the prevalence of synCRLM. Results: The prevalence of synCRLM was significantly higher in patients with NAFLD than that in patients without NAFLD (18.33% vs. 7.42%; χ2=7.669, P=0.006). A logistic regression analysis indicated that NAFLD, CEA, CA19-9 and lymph node status were risk factors for synCRLM, and NAFLD showed the highest hazard ratio (3.930[95% confidence interval: 1.616~9.560]). In NAFLD patients, both fibrosis-4 index (FIB-4) and NAFLD fibrosis score (NFS) were significantly lower in those with synCRLM compared to those without synCRLM [FIB-4: 1.246(0.833~1.276) vs. 1.436(1.016~2.699), Z=-2.130, P=0.033; NFS: -1.282(-2.407~-0.262) vs. -0.255(-1.582~0.755), Z=-2.302, P=0.021; Mann-Whitney test]. Conclusion: NAFLD may be associated with increased liver metastasis, and for NAFLD-related advanced liver fibrosis and cirrhosis may be associated with reduced synchronous liver metastasis in CRC patients. However, the correlation between simple steatosis and steatohepatitis remains to be further determined. Certain factors such as NAFLD, lymph node metastasis, elevated levels of preoperative CEA and CA19-9 are suggesting a high risk of synCRLM.